Răspuns :
a) 3x+5=2║⇒3×(-1)+5=2
x=-1 -3+5=2
2=2(A)⇒X=-1 este solutie
b) -2x+3=5 ║⇒-2×(-1)+3=5
x=-1 2+3=5
5=5(A)⇒X=-1 este solutie
c) -x+3x+5=3║⇒-(-1)+3×(-1)+5=3
x=-1 1-3+5=3
-2+5=3
3=3 (A)⇒ X=-1 este solutie
Succes!!
x=-1 -3+5=2
2=2(A)⇒X=-1 este solutie
b) -2x+3=5 ║⇒-2×(-1)+3=5
x=-1 2+3=5
5=5(A)⇒X=-1 este solutie
c) -x+3x+5=3║⇒-(-1)+3×(-1)+5=3
x=-1 1-3+5=3
-2+5=3
3=3 (A)⇒ X=-1 este solutie
Succes!!
a)3x+5=2
3x=2-5
3x=-3
x=3:3
x=-1
b)-2x+3=5
-2x=5-3=2
-2x=2
x=-1
c)-x+3x+5=3
2x+5=3
2x=3-5
2x=-2
x=2:(-2)
x=-1
3x=2-5
3x=-3
x=3:3
x=-1
b)-2x+3=5
-2x=5-3=2
-2x=2
x=-1
c)-x+3x+5=3
2x+5=3
2x=3-5
2x=-2
x=2:(-2)
x=-1